Onde está a "varinha mágica"?: um estudo compreensivo da relação família, adolescente, sistema de garantia de direitos e rede de atendimento no contexto jurídico - Lugli, Mariana (2009)
The relationship between the family, Children s and Adolescents Rights Guarantee and attendance network is provided. Current research consists of a qualitative investigation undertaken with a family, a judge, a defense lawyer, a psychologist, a minors counselor, a school headmistress and a social worker. Data collection was produced by half-structured interview and a time line. The complex relationships built in the process were provided by the analytic categories constructed by the family s, rights guarantee system representatives and the attendance network s narration. Although the family was aware that it was well attended to by professionals through a series of sessions, the case made no improvement since it first received public attention. The family is hostage to a system of non-coordinated attendances which do not function as a whole. Decreasing the phenomenon s complexity into simple and focused activities, or rather, the permanence of unarticulated separate compartments, failed to offer a real alternative for the family. In fact, the case has been in the Lower Courts for years with no actual solution. When seen from the traditional points of view of the attendants, all the people involved act according to rules and comply with their responsibilities, even though true results for the benefit of the family fail. The construction of competence-generating contexts in the family and in the network s professionals is required. A positive model and an acknowledgement of the groups resources should be established